Factors influencing nurse satisfaction with Automated Medication Dispensing Cabinets - Víctor G. Aguilar-Escobar; Pedro Garrido-Vega; Patricia del Valle Vázquez-Rivas; Antonio Monzón-Moreno (WPOM : Working Papers on Operations Management)
To improve efficiency, quality and safety of medication administration systems, hospitals have been implementing automated dispensing cabinets (ADCs) in healthcare units. The purpose of this study was to evaluate nursing staff’s level of satisfaction with ADCs by analyzing several aspects and differences in perceptions between groups of users. It being a fact that nurses are the end users of the ADC system, their perceptions and opinions are crucial to the success of this technological implementation. A cross-sectional survey was conducted in units with ADCs from a Spanish hospital (n = 97, 32.12%. response rate). Data were analyzed using comparisons between groups and principal component analysis (PCA). The results show that, in general terms, nursing staff have a high degree of satisfaction with ADCs, with order and organization being the most valued aspect. The type of clinical unit and personnel seniority explain some of the differences in valuation. PCA revealed the existence of two general dimensions of nurse satisfaction: efficiency and safety. From this study, conclusions can be drawn to help hospital managers achieve success in implementing ADCs in their centers.